Therapeutic effects of natural compounds against diabetic complications via targeted modulation of ferroptosis - Zhang, Zhen; Li, Luxin; Fu, Wei; Fu, Zhengchao; Si, Mahang; Wu, Siyu; Shou, Yueying; Pei, Xinyu; Yan, Xiaoyi; Zhang, Chenguang; Wang, Tong; Liu, Fei (Frontiers in Pharmacology, 2024)
Diabetes mellitus, a chronic metabolic disorder, can result in serious tissue and organ damage due to long-term metabolic dysfunction, leading to various complications. Therefore, exploring the pathogenesis of diabetic complications and developing effective prevention and treatment drugs is crucial. The role of ferroptosis in diabetic complications has emerged as a significant area of research in recent years. Ferroptosis, a recently discovered form of regulated cell death closely linked to iron metabolism imbalance and lipid peroxidation, has garnered increasing attention in studies exploring the potential role of natural products in its regulation. This review provides an overview of the mechanisms underlying ferroptosis, outlines detection methods, and synthesizes information from natural product databases. It also summarizes current research on how natural products may regulate ferroptosis in diabetic complications. Studies have shown that these products can modulate the ferroptosis process by influencing iron ion balance and combating oxidative stress. This highlights the potential of natural products in treating diabetic complications by regulating ferroptosis, offering a new strategy for managing such complications.